Virtual chromoendoscopy in small bowel capsule endoscopy: new light or a cast of shadow? - Cotter, José de Almeida Berkeley (2014)
AIM: To evaluate whether virtual chromoendoscopy can improve the delineation of small bowel lesions previously detected by conventional white light small bowel capsule endoscopy (SBCE). METHODS: Retrospective single center study. One hundred lesions selected from forty-nine consecutive conventional white light SBCE (SBCE-WL) examinations were included. Lesions were reviewed at three Flexible Spectral Imaging Color Enhancement (FICE) settings and Blue Filter (BF) by two gastroenterologists with experience in SBCE, blinded to each other's findings, who ranked the quality of delineation as better, equivalent or worse than conventional SBCE-WL. Inter-observer percentage of agreement was determined and analyzed with Fleiss Kappa (κ) coefficient. Lesions selected for the study included angioectasias (n = 39), ulcers/erosions (n = 49) and villous edema/atrophy (n = 12). RESULTS: Overall, the delineation of lesions was improved in 77% of cases with FICE 1, 74% with FICE 2, 41% with FICE 3 and 39% with the BF, with a percentage of agreement between investigators of 89% (κ = 0.833), 85% (κ = 0.764), 66% (κ = 0.486) and 79% (κ = 0.593), respectively. FICE 1 improved the delineation of 97.4% of angioectasias, 63.3% of ulcers/erosions and 66.7% of villous edema/atrophy with a percentage of agreement of 97.4% (κ = 0.910), 81.6% (κ = 0.714) and 91.7% (κ = 0.815), respectively. FICE 2 improved the delineation of 97.4% of angioectasias, 57.1% of ulcers/erosions and 66.7% of villous edema/atrophy, with a percentage of agreement of 89.7% (κ = 0.802), 79,6% (κ = 0.703) and 91.7% (κ = 0.815), respectively. FICE 3 improved the delineation of 46.2% of angioectasias, 24.5% of ulcers/erosions and none of the cases of villous edema/atrophy, with a percentage of agreement of 53.8% [κ = not available (NA)], 75.5% (κ = NA) and 66.7% (κ = 0.304), respectively. The BF improved the delineation of 15.4% of angioectasias, 61.2% of ulcers/erosions and 25% of villous edema/atrophy, with a percentage of agreement of 76.9% (κ = 0.558), 81.6% (κ = 0.570) and 25.0% (κ = NA), respectively. CONCLUSION: Virtual chromoendoscopy can improve the delineation of angioectasias, ulcers/erosions and villous edema/atrophy detected by SBCE, with almost perfect interobserver agreement for FICE 1.